Architecture, design, and modeling of the OPSnet asynchronous optical packet switching node - Vanderbauwhede, W.A.; Harle, D.A. (Journal of lightwave technology, 2005)
An all-optical packet-switched network supporting multiple services represents a long-term goal for network operators and service providers alike. The EPSRC-funded OPSnet project partnership addresses this issue from device through to network architecture perspectives with the key objective of the design, development, and demonstration of a fully operational asynchronous optical packet switch (OPS) suitable for 100 Gb/s dense-wavelength-division multiplexing (DWDM) operation. The OPS is built around a novel buffer and control architecture that has been shown to be highly flexible and to offer the promise of fair and consistent packet delivery at high load conditions with full support for quality of service (QoS) based on differentiated services over generalized multiprotocol label switching.